The endogenous glutamatergic transmitter system promotes collagen synthesis in cardiac fibroblasts under hypoxia - Wang, Ruiyu; Yuan, Xiao; Xie, Ting; Zhao, Xin; Li, Junying; Zhang, Xiaohong; Lv, Chuanzhu (Frontiers in Cardiovascular Medicine, 2025)
Excessive collagen production is a hallmark of cardiac fibroblasts (CFs) activation and plays a pivotal role in the pathogenesis of myocardial fibrosis (MF). Hypoxia, a key pathogenic factor in MF, induces aberrant biological responses in CFs and is closely associated with CFs activation. This study investigates the mechanisms underlying hypoxia-induced fibrogenesis from a metabolomics perspective. Neonatal rat CFs were isolated and cultured under normoxic or hypoxic conditions. Hypoxia significantly increased collagen production in CFs, as indicated by the upregulation of Collagen I and Collagen III expression. Non-targeted metabolomics profiling revealed significant alterations in the secretory metabolites of CFs under hypoxia, among which, L-glutamate levels were markedly elevated. Furthermore, L-glutamate concentrations were significantly increased in the myocardial tissues of rats with myocardial infarction. Key components of the glutamatergic transmitter system, including glutamate receptors, metabolic enzymes, and transporters, were detected in CFs, and their expression was upregulated under hypoxic conditions. Notably, exogenous L-glutamate supplementation promoted collagen production in CFs even under normoxia. Blocking glutamate receptors with CNQX and MK-801 effectively reversed hypoxia-induced increases in Collagen I and Collagen III protein expression. Additionally, both CNQX and MK-801 significantly downregulated TGF-β protein expression and Smad2/3 phosphorylation in hypoxia-stimulated CFs. These findings demonstrate that L-glutamate mediates collagen production in CFs under hypoxia, partially through activation of the TGF-β/Smad signaling pathway. Targeting the glutamatergic transmitter system may offer a novel therapeutic strategy for MF.